Galunisertib (LY2157299), a transforming growth factor-β receptor I kinase inhibitor, attenuates acute pancreatitis in rats - Liu, X. (Braz J Med Biol Res, 2016)
Galunisertib (LY2157299), a selective ATP-mimetic inhibitor of TGF-β receptor I (TGF-βRI), is the only known TGF-β pathway inhibitor. In the present study, we investigated the effect of galunisertib on taurocholate (TAC)-induced acute pancreatitis (AP) in rats, and the role of TGF-β and NF-κB signaling pathways. AP was induced by infusion of TAC into the pancreatic duct of Sprague-Dawley male rats (n=30). The rats (220±50 g) were administered galunisertib intragastrically [75 mg·kg(-1)·day(-1) for 2 days (0 and 24 h)]. Serum IL-1β, IL-6, TNF-α, amylase (AMY), lipase (LIP), and myeloperoxidase (MPO) levels were measured by ELISA. NF-κB activity was detected by electrophoretic mobility shift assay (EMSA); NF-κBp65 and TGF-β1 proteins, as well as TGF-βRI and p-Smad2/3 proteins, were detected by western blot assay. Cell apoptosis was detected by TUNEL assay. H&E staining was used to evaluate the histopathological alterations of the pancreas. Galunisertib treatment attenuated the severity of AP and decreased the pancreatic histological score. In addition, number of apoptotic cells were significantly increased in the galunisertib-treated group (16.38±2.26) than in the AP group (8.14±1.27) and sham-operated group (1.82±0.73; P<0.05 and P<0.01, respectively). Galunisertib decreased the expression levels of TGF-βRI and p-Smad2/3 and inhibited NF-κB activation and p65 translocation compared with the sham-operated group. Furthermore, serum IL-1β, IL-6, TNF-α, AMY and LIP levels and tissue MPO activity were significantly decreased in the galunisertib-treated group. Our data demonstrate that galunisertib attenuates the severity of TAC-induced experimental AP in rats by inducing apoptosis in the pancreas, inhibiting the activation of TGF-β signals and NF-κB as well as the secretion of pro-inflammatory cytokines.